[1914 Sophomore Men's Basketball Team] - Frank Aston::::::photographer::: (1914)
Group portrait sophomore (Class of 1917) basketball team; basketball painted with 'SOPH '17' [subjects in 2 rows - kneeling, standing] Basketball competitions between classes won by Sophomores (Class of 1917) in 1914.